Patient experiences of waiting for orthopaedic care and priorities for ‘waiting well’: a qualitative study in a London NHS trust - Jodie Chan; Sharon Poon; Anna Lawrence-Jones; Fiona O’Driscoll; Carol Waugh; Abiola Awojobi-Johnson; Leila Shepherd; Kate Grailey (Archives of Public Health)
Abstract Background Following the COVID- 19 pandemic, patients are facing larger waiting lists and longer waiting times than ever before. Long waits for orthopaedic treatment can negatively impact patients’ quality of life due to pain, reduced mobility, and the psychological effects of waiting itself. Initial analysis at a London National Health Service (NHS) Trust showed that patients living in the most deprived areas were more likely to face longer waiting times for joint replacement surgery. This study aimed to understand what would support people to live well while waiting for orthopaedic treatment, focusing on those in the most deprived areas. Methods We conducted semi-structured interviews with patients living in deprived areas in North West London who were currently waiting or had recently waited over 18 weeks for an orthopaedic procedure. Data were analysed using inductive thematic analysis. Key insights from this analysis were brought to a co-design workshop, where patients developed targeted and bespoke support initiatives and identified how these might help people to live well while waiting. We worked with two public partners throughout, who shaped the interview questions, analysis, and workshop. Results Seven patients were interviewed, and a further six patients participated in the co-design workshop. The interviews identified four immediate impacts of waiting on wellbeing, including physical pain, limitations on daily activities, greater reliance on friends and family, and anxiety around the wait; as well as four long-term consequences of an extended wait time, including physical deterioration, delays of life plans, changes in hopefulness, and reduced trust in the NHS. Additionally, they identified four sub-themes around patients’ support needs while waiting: medical support, practical support, informational support, and emotional support. Based on these thematic insights, patients at the workshop developed four potential interventions to support people waiting for orthopaedic treatment. Conclusion This study highlights the negative impacts that prolonged waits for orthopaedic treatment can have on patients’ physical, mental, and social wellbeing, and notes that patients with caring or financial responsibilities may be disproportionately affected. The support needs expressed by patients focused more on acknowledgement of their concerns and management of their expectations by health professionals, rather than on advice around lifestyle changes and coping mechanisms. Our study offers a number of support ideas proposed by patients which can be further developed and implemented by health services to better support patients to live well while waiting for orthopaedic treatment.